Mechanisms of mitochondrial fusion and fission - Scorrano, Luca (Henry Stewart Talks, 2007)
Mitochondrial ultrastructure, Mitochondrial organization in the cytosol, Mitochondria-shaping proteins, Dynamins and the dynamin superfamily, Control of mitochondrial shape in yeast, Control of mitochondrial morphology in mammals, Mitochondrial fusion and the transmission of mitochondrial DNA, Changes in mitochondrial ultrastructure during apoptosis, Mitochondrial fragmentation during apoptosis, Cristae remodeling and OPA1
Archived at 2018/05/31